Understanding Responsible Leadership: Role Identity and Motivational Drivers - Pless, Nicola M. (Journal of business ethics, 2007)
This article contributes to the emerging discussion on responsible leadership by providing an analysis of the inner theatre of a responsible leader. I use a narrative approach for analyzing the biography of Anita Roddick as a widely acknowledged prototype of a responsible leader. With clinical and normative lenses I explore the relationship between responsible leadership behavior and the underlying motivational systems. I begin the article with an introduction outlining the current state of responsible leadership research and explaining the kind of magnifying glasses used to examine the case. I continue with a brief summary of Anita Roddick’s development from childhood to adulthood, which provides the biographical background for exploring her motivational systems as a leader. Against this backdrop, I analyze the relationship between motivational drivers and a responsible leadership identity as revealed by Roddick in different behavioral leadership roles. I conclude the article by providing a number of lessons learned for responsible leadership and the development of future global leaders.